Factors Associated with Successful Completion of the Chronic Disease Self-Management Program among Middle-Aged and Older Asian-American Participants: A National Study - Ahn, SangNam; Smith, Matthew Lee; Cho, Jinmyoung; Jiang, Luohua; Post, Lindsey; Ory, Marcia G. (Frontiers in Public Health, 2015)
Asian-Americans are a small but fast-growing population in the United States who are increasingly experiencing multiple chronic diseases. While the evidence-based Chronic Disease Self-Management Program (CDSMP) has been disseminated among various racial and ethnic populations, few studies specifically investigate participants with an Asian background. The study aims to identify characteristics of middle-aged and older Asian-American CDSMP participants (older than 50 years) and investigate factors related to successful workshop completion (i.e., attending 4+ of the 6 sessions) among this population. Data were analyzed from 2,716 middle-aged and older Asian-Americans collected during a 2-year national dissemination of CDSMP. Multilevel logistic regression analyses were conducted to identify individual- and workshop-level covariates related to successful workshop completion. The majority of participants were female, living with others, and living in metro areas. The average age was 71.3 years old (±9.2), and the average number of chronic conditions was 2.0 (±1.5). Successful completion of CDSMP workshops among participants was associated with their number of chronic conditions (OR = 1.10, P = 0.011), living in non-metro areas (OR = 1.77, P = 0.009), attending workshops from area agencies on aging (OR = 1.56, P = 0.018), and attending a workshop with higher completion rates (OR = 1.03, P < 0.001). This study is the first large-scale examination of Asian-American participants enrolled in CDSMP and highlights characteristics related to intervention attendance among this under-studied minority population. Knowing such characteristics is important for serving the growing number of Asian-Americans with chronic conditions.